Analysis of factors influencing the efficacy of NAC and prognosis between HER2-zero and HER2-low HR negative breast cancer - Liu, Jing-Jing; Zhang, Yi; Zhang, Shi-Chao; Liu, Xu; Wang, Shu-Nan; Liu, Xin-Yu; Zhang, Jin (Frontiers in Cell and Developmental Biology, 2024)
Objective: The aim of this paper was to assess the differences in clinicopathological characteristics, efficacy and prognosis of neoadjuvant chemotherapy (NAC) in human epidermal growth factor receptor2(HER2)-zero and HER2-low hormone receptor (HR)-negative breast cancer (BC) patients, and the impact of HER2-evolution on prognosis before and after NAC.Methods: 319 triple negative breast cancer (TNBC) patients who completed NAC and surgery from August 2014 to August 2018 at Tianjin Medical University Cancer Institute and Hospital were included. Clinicopathological features, efficacy of NAC and assessment of prognosis were retrospectively analysed. The evolution of HER2-zero to HER2-low after NAC is defined as HER2-gain, the evolution of HER2-low to HER2-zero after NAC is defined as HER2-loss, and HER2 unchanged after NAC is defined as HER2-stable.Results: In HR-negative BC, the pathological complete response (pCR) rate was significantly higher in HER2-zero compared with HER2-low patients, and the difference was statistically significant (38.9% vs 23.2%, p = 0.004), but there was no significant difference in the prognosis between the two groups. The overall rate of HER2-evolution after NAC was 19.7%, and there was a significant correlation between HER2-loss and histological grading, whereas HER2-gain was significantly associated with Ki-67 expression. In terms of prognosis, HER2-gain was better compared to the other two groups.Conclusion: In this study, we found that HER2-low HR-negative BC showed different clinicopathological features and response to NAC compared with HER2-zero, as well as HER2-evolution before and after NAC had a significant impact on prognosis.